The role of shoulder and chamfer margin design on the fracture resistance of zirconia crown - Corentus Leo, Andri; Ariyani; Syafrinani (Indonesian Journal of Prosthodontic, 2024)
In recent years, zirconia all-ceramic restorations are widely used in crown and bridge treatment due to their superior mechanical properties and aesthetics. Zirconia is the strongest ceramic material, thus it is the treatment of choice for posterior dental restorations. One factor that affects the fracture resistance of zirconia restoration is the margin design. The shoulder and chamfer are the recommended margin design to obtain maximum fracture resistance from zirconia restoration. Shoulder is recommended because it has greater fracture resistance while chamfer is more conservative and able to withstand maximum masticatory load. However, there is still a difference of opinion regarding the fracture resistance of zirconia crown with shoulder and chamfer margin designs. This literature review aims to discuss the role of chamfer and shoulder margins design on the fracture resistance of zirconia crown. The shoulder margin design results in a wide ledge, space for adequate restoration contours and maximum aesthetics that provide resistance to occlusal forces and minimizes stress that can cause fracture. The chamfer margin design on zirconia crown has a difference in the rounded internal angle of the preparation resulting in better force distribution, better marginal fit and more resistance to fracture compared to the shoulder margin design. Chamfer margin design is more conservative and resistant to fracture due to better marginal fit which distribute stress more evenly. Keywords: zirconia, margin design, chamfer, shoulder, fracture resistance